Handling disrupted learning during covid-19 pandemic: learners' experience in Nigeria / Folashade Afolabi - Afolabi, Folashade (Research Management Centre (RMC), 2020)
Coronavirus has affected not only the human health but also the educational sector. As a result of this pandemic, schools were forced to suspend face-to-face learning and implement an alternative method of learning which is online learning. The focus of this paper is to investigate the accessibility and efficiency of learning during the lockdown period. The paper examined the effectiveness of vodcast (video and podcast) lessons as a strategy in online teaching by using learning management system (LMS) and to what extent the strategy met the needs of the learners during the challenging period of the covid-19 pandemic. The study adopted mixed method research which consisted of three main phases of design. The questionnaire used in this study comprises 15 items and is divided into two sections and 50 participants participated in the study. The findings indicated that learners displayed positive perceptions towards the use of vodcast lessons during the pandemic period. Furthermore, they reported that online learning should be used to complement face-to-face teaching even after the pandemic period is over.